The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1001/jamaoncol.2023.6552
|View full text |Cite
|
Sign up to set email alerts
|

Induction Chemotherapy Followed by Radiotherapy vs Chemoradiotherapy in Nasopharyngeal Carcinoma

Jinxuan Dai,
Bin Zhang,
Yixin Su
et al.

Abstract: ImportanceInduction chemotherapy plus concurrent chemoradiotherapy is recommended for locoregionally advanced nasopharyngeal carcinoma but is associated with higher rates of acute toxic effects and low compliance. Evidence on de-escalating treatment intensity after induction chemotherapy is limited.ObjectiveTo assess if radiotherapy was noninferior to chemoradiotherapy after induction chemotherapy for locoregionally advanced nasopharyngeal carcinoma.Design, Setting, and ParticipantsFrom April 2015 to March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Second, this study did not provide subgroup analysis for different stages. Such information would be crucial to identify the specific patients suitable for the disintensified treatments in clinical practice because this study enrolled patients with heterogeneous stages encompassing III to IVB.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Second, this study did not provide subgroup analysis for different stages. Such information would be crucial to identify the specific patients suitable for the disintensified treatments in clinical practice because this study enrolled patients with heterogeneous stages encompassing III to IVB.…”
mentioning
confidence: 94%
“…To the Editor A recent randomized clinical trial reported that after induction chemotherapy (IC), patients with stages III to IVB ( American Joint Committee on Cancer Staging Manual, 7th Edition ) nasopharyngeal carcinoma (NPC) receiving radiation therapy alone had noninferior oncologic outcomes and fewer acute adverse events, compared with those receiving concurrent chemoradiotherapy (CCRT). We have several comments about this impactful study.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…To the Editor We read the article by Dai et al with great interest. Omitting chemotherapy in patients receiving induction chemotherapy (IC) is a hot topic in nasopharyngeal carcinoma treatment, particularly in the intensity-modulated radiotherapy era.…”
mentioning
confidence: 99%
“…In Reply We appreciate the comments made by Lee et al and Bayatfard et al on our recent article . We applied concurrent cisplatin in the conventional 30-mg/m 2 dose weekly when we designed this trial.…”
mentioning
confidence: 99%